2021
DOI: 10.5334/joc.136
|View full text |Cite
|
Sign up to set email alerts
|

Why Does Dual-Tasking Hamper Implicit Sequence Learning?

Abstract: Research on the limitations of dual-tasking might profit from using setups with a predictable sequence of stimuli and responses and assessing the acquisition of this sequence. Detrimental effects of dual-tasking on implicit sequence learning in the serial reaction time task (SRTT; Nissen & Bullemer, 1987)-when paired with an uncorrelated task-have been attributed to participants' lack of separating the streams of events in either task. Assuming that co-occurring events are automatically integrated, we reasoned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 68 publications
2
26
0
Order By: Relevance
“…The findings revealed that implicit learning was preserved for the fixedly, but hampered for the variably paired SRTT-tone combinations. Again, this finding suggests that the participants integrate the stimuli of the two tasks before they then can learn something about the sequence built into the SRTT (see also Röttger et al, 2021).…”
Section: Task Integration In Dual-taskingmentioning
confidence: 85%
See 3 more Smart Citations
“…The findings revealed that implicit learning was preserved for the fixedly, but hampered for the variably paired SRTT-tone combinations. Again, this finding suggests that the participants integrate the stimuli of the two tasks before they then can learn something about the sequence built into the SRTT (see also Röttger et al, 2021).…”
Section: Task Integration In Dual-taskingmentioning
confidence: 85%
“…Several findings in the field of dual-tasking suggest that the participants tend to integrate the two tasks within a trial into one single task-set when the stimuli of these tasks are presented in temporal proximity (Schumacher & Hazeltine, 2016 ; Röttger et al, 2019 , 2021 ; Schmidtke & Heuer, 1997 ; Zhao et al, 2020 ). The goal of the current study was to examine whether the generation of joint memory episodes might be a conceivable mechanism underlying task integration (Logan, 1988 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a performance-reducing influence of the secondary task was not found during sequence retrieval, which the authors explained with the availability of an abstract representation of the sequence, which makes the primary task invulnerable to dual-tasking interference. Röttger et al (2021) investigated the disruption of learning in a visual-manual serial reaction time task by interference with a secondary auditory-vocal task. By creating probabilistic pairings between stimulus features in the serial-reaction time task and in the secondary task, the authors demonstrated that across-task contingencies facilitate learning in the primary task despite any imposed dual-task demands.…”
mentioning
confidence: 99%